The British presence in the Malay world: a meeting of civilizational traditions - López C., Carolina (Universiti Kebangsaan Malaysia, 2001)
This article examines points of convergence and divergence in values, assumptions and interpretations underlying historical encounters between the British and the Melayu traditions in colonial Malaya. It proposes that in addition to examining power relations between them, it is necessary to uncover the largely unconscious paradigmatic assumptions causing them to view and value the same phenomena in radically different ways. The basic proposition of the study is that the British colonizers and the Melayu brought different internalized filters within themselves to the critical junctures – or the actual encounters occurring between the two groups. These differences in interpretative mechanisms, held largely below the level of consciousness, constitute an often unexamined source of tension and misunderstanding among groups from diverse traditions. It is the author’s hope that attention given to convergence and divergence in underlying values and interpretative mechanisms may be of use in resolving conflict between different traditions, which presently pose a grave challenge to the world today